Theoretical and Methodological Framework for Studying Video Games and Orientalism - Šisler, Vít (CyberOrient, 2023)
This article proposes a theoretical and methodological framework for studying orientalism and representation in video games, grounded in information science, communication studies, game studies, and cultural studies. Utilizing the approaches of critical transculturalism, game production studies, and a newly refined concept of gamevironments, the proposed framework understands video games as hybrid cultural artifacts existing within interconnected technical, socio‐cultural, political, economic, and religious spheres. It examines games on three levels: as computational systems encompassing procedural, narrative, and audiovisual layers; as designed by authors encoding worldviews and ideas; and as dynamically interpreted by players. Encompassing the contexts influencing design and reception, this framework enables nuanced analysis of how games perpetuate or challenge orientalist discourses. Methodologically, it integrates techniques from across disciplines to study games' components, creators, audiences, and wider environments. Using Arab and Iranian gaming cultures as an example, this article highlights applying the framework to local productions negotiating global media flows and political constraints. Overall, it aims to offer an expansive and multifaceted toolkit for researching orientalism, representation, and identity construction in video games.